Heterologous Expression, Biosynthetic Studies, and Ecological Function of the Selective Gq‐Signaling Inhibitor FR900359. Issue 3 (20th December 2017) - Crüsemann, Max; Reher, Raphael; Schamari, Isabella; Brachmann, Alexander O.; Ohbayashi, Tsubasa; Kuschak, Markus; Malfacini, Davide; Seidinger, Alexander; Pinto‐Carbó, Marta; Richarz, René; Reuter, Tatjana; Kehraus, Stefan; et al.
Abstract: The cyclic depsipeptide FR900359 (FR), isolated from the tropical plant Ardisia crenata, is a strong and selective inhibitor of Gq proteins, making it an indispensable pharmacological tool to study Gq‐related processes, as well as a promising drug candidate. Gq inhibition is a novel mode of action for defense chemicals and crucial for the ecological function of FR, as shown by in vivo experiments in mice, its affinity to insect Gq proteins, and insect toxicity studies. The uncultured endosymbiont of A .  crenata was sequenced, revealing the FR nonribosomal peptide synthetase ( frs ) gene cluster. We here provide a detailed model of FR biosynthesis, supported by in vitro enzymatic and bioinformatic studies, and the novel analogue AC‐1, which demonstrates the flexibility of the FR starter condensation domains. Finally, expression of the frs genes in E .  coli led to heterologous FR production in a cultivable, bacterial host for the first time. Abstract : The nonribosomal peptide FR900359, a potent Gq protein inhibitor made by an obligate plant symbiont, was heterologously produced in E. coli . The biosynthesis of FR was investigated in vitro and by computations, and an ecological role as a defense chemical against herbivores was defined for FR by investigating the effects of the compound on insects and mice.